2020
DOI: 10.20473/jgs.14.2.2020.257-274
|View full text |Cite
|
Sign up to set email alerts
|

State Capacity and Public Trust in Handling the COVID-19 Outbreak in Malaysia

Abstract: Respon negara-negara terhadap pandemi global sangatlah beragam. Kebijakan yang diambil pemerintah dan dukungan dari masyarakat sangat menentukan keberhasilan penanganan pandemi tersebut. Ada beberapa negara yang cukup lama berjuang melawannya sehingga memiliki implikasi ekonomi yang serius. Tetapi, ada juga negara yang secara efisien mengatasinya sehingga mampu menghambat melonjaknya jumlah penderita Covid-19 dan  melindungi ekonomi negaranya. Selain Selandia Baru, Taiwan dan China,  Malaysia termasuk salah sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Other research, such as in the context of Europe and United States, has also found a correlation between low public trust towards the government as a result of the circulating misinformation (Cardenas, 2022). This in line with the findings of previous studies where there has been found to be a significant correlation between misinformation and public trust, which resulted in a disruption to the available power relations (Agley & Xiao, 2021;Bromme et al, 2022;Ladiqi, 2020;Ledford et al, 2022;Mihelj et al, 2022;Wirawan et al, 2021). In another study which talks about the context of COVID-19 medicine, there are currently no conclusive proof that herbal medicine can eliminate the cause of infection.…”
Section: Discussionsupporting
confidence: 87%
“…Other research, such as in the context of Europe and United States, has also found a correlation between low public trust towards the government as a result of the circulating misinformation (Cardenas, 2022). This in line with the findings of previous studies where there has been found to be a significant correlation between misinformation and public trust, which resulted in a disruption to the available power relations (Agley & Xiao, 2021;Bromme et al, 2022;Ladiqi, 2020;Ledford et al, 2022;Mihelj et al, 2022;Wirawan et al, 2021). In another study which talks about the context of COVID-19 medicine, there are currently no conclusive proof that herbal medicine can eliminate the cause of infection.…”
Section: Discussionsupporting
confidence: 87%
“…This affects the trust and participation of citizens. Several studies have also shown a correlation between government capacity and community participation (Kuipers et al, 2020;Ladiqi, 2020;Mujani, 2020;Mujani & Irvani, 2020). For more than six months, the author observed that the participation of the citizens of Bandung City in the form of non-compliance increased.…”
Section: Results and Discussion Political Noise In Crisismentioning
confidence: 91%
“…Public trust in the government is essential in order to cope with the pandemic. Francis Fukuyama in (Ladiqi, 2020)explained that there are 3 (three) important aspects when a country must be present to save its citizens from a pandemic. These aspects are the state's capacity (state capacity), public trust (social trust), and leadership.…”
Section: Introductionmentioning
confidence: 99%